Epigondolella abneptis and E. spatulata in the Lower Norian in the central Kamnik Alps, Slovenia - Ramovš, Anton (Geologija, 1993)
Epigondolella abneptis (Huckriede, 1958) and E. spatulata (Hayashi, 1968) from the Lower Norian (Upper Triassic) deeper marine micritic limestones with chert nodules and lenses in the locality Sleme, central Kamnik Alps, are presented.